When DNA Polymerases Multitask: Functions Beyond Nucleotidyl Transfer - Carvajal-Maldonado, Denisse; Drogalis Beckham, Lea; Wood, Richard D.; Doublié, Sylvie (Frontiers in Molecular Biosciences, 2022)
DNA polymerases catalyze nucleotidyl transfer, the central reaction in synthesis of DNA polynucleotide chains. They function not only in DNA replication, but also in diverse aspects of DNA repair and recombination. Some DNA polymerases can perform translesion DNA synthesis, facilitating damage tolerance and leading to mutagenesis. In addition to these functions, many DNA polymerases conduct biochemically distinct reactions. This review presents examples of DNA polymerases that carry out nuclease (3' – 5' exonuclease, 5' nuclease, or end-trimming nuclease) or lyase (5' dRP lyase) extracurricular activities. The discussion underscores how DNA polymerases have a remarkable ability to manipulate DNA strands, sometimes involving relatively large intramolecular movement.